PERAN KEPUASAN KERJA MEMEDIASI PENGARUH QUALITY OF WORK LIFE TERHADAP KINERJA KARYAWAN - Aprilia Santika, Si Luh Made Dwi; Kartika Dewi, Anak Agung Sagung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023DO - 10.24843/EEB.2023.v12.i03.p15, 2023)
Employee performance very important for a company, because performance is one of the main things in a company to help achieve company goals and be able to compete in business development. Good or bad employee performance is influenced by many factors, such as quality of work life and job satisfaction. This study to analyze role of job satisfaction in mediating the effect of quality of work life on the performance. The number samples used was 66 employees using a saturated sample. Data collection in this study was carried out by interview and questionnaire methods. The data analysis technique used in this research is Classic Assumption Test, Path Analysis and Sobel Test. Based on results of analysis it was found that the quality of work life has a positive and significant effect on employee performance, quality of work life has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect, job satisfaction mediates the effect of quality of work life on employee performance. The results of this study have implications for human resource development, especially for management to pay more attention to the quality of work life and employee job satisfaction, to improve employee performance.